A Novel Nonlinear Fault Tolerant Control for Manipulator under Actuator Fault. (14th October 2018) - Zhao, Jing; Jiang, Sen; Xie, Fei; He, Zhen; Fu, Jian
Abstract : A fault tolerant control (FTC) scheme based on adaptive sliding mode control technique is proposed for manipulator with actuator fault. Firstly, the dynamic model of manipulator is introduced and its actuator faulty model is established. Secondly, a fault tolerant controller is designed, in which both the parameters of actuator fault and external disturbance are estimated and updated by online adaptive technology. Finally, taking a two-joint manipulator as example, simulation results show that the proposed fault tolerant control scheme is effective in tolerating actuator fault; meanwhile it has strong robustness for external disturbance.